Asceza w doświadczeniu duchowym Teresy z Lisieux oraz Teresy z Los Andes - Hadryś, Jacek (Wydział Teologiczny UAM, 2010)
The Servant of God John Paul II beatified and canonized Juanita, or Teresa of Jesus ‘of Los Andes’ (Chile) and declared Therese of the Child Jesus Doctor of the Church. The two Carmelites lived almost concurrently and were called to eternity at a young age. They shared not only a Carmelite vocation but also a deep spiritual life. The latter defines the aim of the article: to show the place and character of ascesis in the spiritual experience of each of the two, and to bring out relevant similarities and differences. The results of the study are presented in three aspects: motivations of the ascetic effort, inner overcoming of oneself, and external practices of mortification. Both saints practiced ascesis only on account of Christ, and as demonstrated in the article, all their other motivations issued from their love for Christ, and confirmed and developed this love.
Ascesis in the Spiritual Experience of Therese of Lisieux and Teresa de Los Andes
Keywords: Christ; ascesis; Carmel; mortification